Lógica matemática no ensino médio: uma proposta para mobilizar raciocínios - Martins Neto, Raimundo de Souza (2008)
This work has the purpose of establishing how far it is possible to develop the high school students skills concerning the power and the ability of using the rules of classical logic through activities that mobilize thoughts, using the logical connective: negation, conjunction, disjunction, implication, biconditional and quantitative. The logical reasoning, regarding the origin, use and development, are analyzed and interpreted in the light of the theoreticians Piaget and Vygotsky. The activities were prepared based and on adapted the structure offered by the applet, and applied to students from the second year of high school, during seven meetings. The development, the implementation and analysis met the methodology of teaching engineering, making, firstly, a prior analysis, implementation and, also, a subsequent analysis. The application and the subsequent analysis confirmed our predictions indicating difficulty student s with the use of logical connective, however they showed that the activities have promoted an imbalance between what student has knowledge these of connectives and how he uses them in context and in the classic logic context. It shows that is possible to work classic logic in the high school level